The Habit of Poisoning: The Case of Air Pollutants in the City of Guadalajara, Mexico - Peniche-Camps, Salvador (2020)
[Introduction]: “The risk society” established a useful theoretical framework to understand contemporary society’s perception and the way it addresses Mexico's environmental and political model through the city’s urban development. This situation is present in the most important cities in Latin America. [Objective]: to analyze the case of the incidence of lung diseases in the city of Guadalajara, Jalisco, Mexico, and its correlation with air pollution levels, criticizing the scope and meaning of the air pollution control policy. [Methodology]: The study area was delimited where the State Committee of Epidemiological Surveillance (SCES) of the state of Jalisco recorded the highest incidence of Acute Respiratory Infections (ARIs) in the first 26 weeks of 2018, which harm mainly to children and older adults. These infections were analyzed using the multiple regression model through data obtained from the Jalisco Atmospheric Monitoring System (JAMS), which have the concentrations of the polluters’ criteria that regulate the Mexican Normativity (NOM). [Results]: A significant correlation was obtained (p-value <0.05) for carbon monoxide (CO) = 0.007, ozone (O3) = 0.037, and particles smaller than 10 microns (PM10) = 0.003, which interfere in greater way to the ARIs. [Conclusions]: Ignoring the real possibility of public health effects of the urban population arising from the concentration of pollutants in the air constitutes a limitation of the public health and environmental policy. Based on Beck's risk society theory.